Analisis Yuridis Kebijakan Politik Luar Negeri Indonesia Dalam Mendukung Kedaulatan Palestina Perspektif Siyasah Dauliyah - Monica Putri Syakira; Luthfi Fahrul Rizal; Muhammad Amin (Universitas Cokroaminoto Yogyakarta, 2027)
This study analyzes Indonesia's foreign policy in supporting Palestinian sovereignty through juridical aspects and the Siyasah dauliyah perspective. With an analytical descriptive method with a normative juridical approach, The results indicate that Indonesia's support possesses strong juridical legitimacy, aligning with constitutional mandates and the